Pathogenetic Role of Cholesterol and Triglyceride Metabolic Disturbances in the Development of Critical Conditions - S. A. Perepelitsa; O. V. Sednev (Общая реаниматология)
The review considers mechanisms for the development of respiratory failure caused by lipid metabolic disturbances. It gives data on the lung surfactant composition and lipid imbalance in severe concomitant injury, sepsis, and gestosis. Information on the prenatal and postnatal synthesis of triglycerides and cholesterol is detailed.